2012
DOI: 10.1126/scitranslmed.3003142
|View full text |Cite
|
Sign up to set email alerts
|

Revolution Stalled

Abstract: Drug discovery is at a near standstill for treating psychiatric disorders such as schizophrenia, bipolar disorder, depression, and common forms of autism. Despite high prevalence and unmet medical need, major pharmaceutical companies are deemphasizing or exiting psychiatry, thus removing signif cant capacity from ef orts to discover new medicines. In this Commentary, I develop a view of what has gone wrong scientif cally and ask what can be done to address this parlous situation. Fig. 1. Terrible thing to wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
184
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 29 publications
1
184
0
4
Order By: Relevance
“…1 This idea remains well within the current bench to bedside paradigm. Insel takes a different tack 2 by optimistically emphasizing that many unexplored targets remain: ''…one conspicuous observation from the genetics of mental disorders is that none of the scores of candidates from genome-wide association studies (GWAS) involve the usual psychopharmacologic suspects, monoamine transporters or receptors… interesting candidates emerge.…”
Section: The Bench To Bedside Modelmentioning
confidence: 89%
See 2 more Smart Citations
“…1 This idea remains well within the current bench to bedside paradigm. Insel takes a different tack 2 by optimistically emphasizing that many unexplored targets remain: ''…one conspicuous observation from the genetics of mental disorders is that none of the scores of candidates from genome-wide association studies (GWAS) involve the usual psychopharmacologic suspects, monoamine transporters or receptors… interesting candidates emerge.…”
Section: The Bench To Bedside Modelmentioning
confidence: 89%
“…1 Molecular ''targets'' such as the serotonin and norepinephrine receptors are affected within minutes by psychotropic agents, whereas clinical benefit takes several weeks. Such ''targets'' are only the first domino.…”
Section: The Bench To Bedside Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2014.11a2 reporting the O'Brien study referenced here.). As Steven Hyman puts it -in a paper entitled 'revolution stalled' -this is largely because of an inability to demonstrate efficacy (Hyman, 2012). Hence the paradox -more and more people are taking the drugs, especially for relatively minor problems of mental health -while the hypothesis on which they are based is no longer viable.…”
Section: Crisis Of Treatmentmentioning
confidence: 99%
“…In another example, genome-wide association studies in large population samples have revealed genetic loci linked to psychiatric disorders such as schizophrenia [7]. Perhaps the functional effects of these genetic changes will reveal a phenotype (e.g., decreased synaptic function in neuronal subtypes) against which new compounds can be screened [8]. This "phenotypic screening" method for drug discovery, which focuses on correcting a biological signature associated with the disease process rather than targeting a specific protein, has been widely used in other fields [9].…”
Section: Outcome-oriented Approachmentioning
confidence: 99%